Teacher communication and the role of language use in the primary mathematics classroom discourse / Liew Kee Kor and Chap Sam Lim - Liew, Kee Kor; Chap, Sam Llim (Universiti Teknologi MARA, Kedah, 2016)
Language is central to learning and acts as a medium or a tool through which new learning is assimilated and defined.The teaching and learning of mathematics which mediated by language is complicated in a multilingual context. This paper reports a study that explored the communication and language use in a multicultural Malaysian primary mathematics context. The aim of this study was twofold. Firstly, it investigated the language use by teachers in the mathematics classroom discourse, and secondly, it studied the roles of language use by the teachers in teaching mathematics. Six mathematics teachers from three types of primary schools participated in this study. Data were collected by video recording 12 classroom lessons and interview with each teacher after each lesson. Results showed that language use in the three types of primary schools mathematics classroom reflects the ethnicity of the pupils in the schools. In the weaker classes, both novice and expert teachers, in particular, those from the Chinese schools switched from English to pupils' spoken language to teach for understanding. It was also observed that language use assumed different roles in the mathematics discourse. The three important roles identified are: for explaining, questioning and discussing among peers. This paper concludes with some implications for language use in primary school mathematics within a bi/multilingual context.